Efektivitas Terapi Seni (Art Therapy) Terhadap Ekspresi Emosi Pada Pasien Dengan Gangguan Jiwa - Zaenal, Zaenal; Rosida, Rosida (Barongko: Jurnal Ilmu Kesehatan, 2025)
Mental disorders are commonly associated with difficulties in regulating and expressing emotions, which may lead to maladaptive behaviors such as withdrawal, aggressiveness, or excessive anxiety. One of the non-pharmacological interventions that can help patients cope with these difficulties is art therapy, a therapeutic approach that utilizes visual art activities to facilitate the safe and constructive expression of emotions. This study aims to evaluate the effectiveness of art therapy on emotional expression among patients with mental disorders. A quasi-experimental design with a pretest-posttest control group was employed. The sample consisted of 40 patients, divided into an intervention group (n=20) who received art therapy twice a week for 4 weeks, and a control group (n=20) who received routine care only. Emotional expression was measured using a modified Emotional Expression Scale (EES). Data were analyzed using paired t-test and independent t-test. The results showed a significant improvement in emotional expression scores in the intervention group (mean score increased from 45.3 to 72.8; p=0.001), while the control group showed no significant change (46.1 to 48.0; p=0.356). Post-intervention comparisons between groups indicated a statistically significant difference (p=0.004). In conclusion, art therapy is proven to be effective in enhancing emotional expression among patients with mental disorders. This intervention may serve as a simple, enjoyable, and safe strategy in psychiatric rehabilitation programs.